2023
DOI: 10.1039/d2sc05541d
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-empowered cis-diol metabolic fingerprinting enables precise diagnosis of primary liver cancer

Abstract: A mass spectrometric platform was built for in-depth profiling of mutational landscape of cis-diol metabolites from the healthy to primary liver cancer (PLC) patients. This method enabled more precise PLC diagnosis than protein marker-based methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The data were calculated by normalization, and then visualized by applying pattern recognition methods, such as partial least squares (PLS), 21,22 orthogonal partial least squares (OPLS), 23,24 and the variable influence on projection approach for O2PLS (R) models, which is a model-based method for judging the importance of variables; its cornerstone is the 2-way formalism of the O2PLS models. 25 The study used Simca-p 12.0 to construct the model by OPLS and O2PLS when analysing a dependent variable or multiple dependent variables, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The data were calculated by normalization, and then visualized by applying pattern recognition methods, such as partial least squares (PLS), 21,22 orthogonal partial least squares (OPLS), 23,24 and the variable influence on projection approach for O2PLS (R) models, which is a model-based method for judging the importance of variables; its cornerstone is the 2-way formalism of the O2PLS models. 25 The study used Simca-p 12.0 to construct the model by OPLS and O2PLS when analysing a dependent variable or multiple dependent variables, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This property is advantageous for selectively enriching cis -diols from complex matrices. 120 However, when it comes to reporting precise information in diagnostic methods, the lack of specificity hinders the ability to precisely identify and differentiate between specific glycan structures.…”
Section: Traditional Glycan Binding Receptorsmentioning
confidence: 99%
“…Their dysregulation has been noted in many complex diseases, such as cancer and diabetes. A 2023 study demonstrated the ability of machine learning to interpret cis-diol metabolic fingerprinting for precise diagnosis of primary liver cancer [30]. Ge et al recently discovered VIPR1 as an early diagnostic biomarker through machine learning from microarray datasets [31].…”
Section: Ai-assisted Biomarker Detectionmentioning
confidence: 99%